An investigation of Monte Carlo tree search and local search for course timetabling problems - Goh, Say Leng (2017)
The work presented in this thesis focuses on solving course timetabling problems, a variant of education timetabling. Automated timetabling is a popular topic among researchers and practitioners because manual timetable construction is impractical, if not impossible, as it is known to be NP-hard.